Evaluation of novel approaches to software engineering : 10th International Conference, ENASE 2015, Barcelona, Spain, April 29-30, 2015, Revised selected papers /: 10th International Conference, ENASE 2015, Barcelona, Spain, April 29-30, 2015, Revised selected papers. (2016) - Unknown
No abstract available